Resource Allocation and Strategy - Maritan, Catherine A.; Lee, Gwendolyn K. (Journal of Management, 2017)
Resource allocation is fundamental to strategic management. Yet, surprisingly, there is not a large body of literature specifically about the allocation of financial, physical, technological, and human resources that support firm strategies. This special issue seeks to bring renewed attention to resource allocation as an important topic for strategy research. The curated set of articles and commentaries offer conceptual and empirical contributions that assess the current state of research on the topic, present analyses and new insights, and propose promising directions for future research. Through this special issue, we hope to encourage more research that examines resource allocation as a central focus of study for achieving deeper and better understandings about firm strategies.